Dielectric Characteristics of Pt/BaxSr1-xTiO3/Pt Thin Film Structure under the Electron Beam Irradiation - V. V. Buniatyan; V. M. Tsakanov; N. W. Martirosyan; G. S. Melikyan; H. R. Dashtoyan
The dielectric properties of aBa0.25Sr0.75TiO3films with Pt interdigitated electrodes fabricated by pulsed laser deposition technique and examined under the low-energy electron beam irradiation. The structures were characterized by means of dielectric permittivity,ε-f, C-f, tgδ-f dependencies before and after irradiation over frequency range from 100 Hz to 1 MHz. Irradiations have been carried out in AREAL (Advanced Research Electron Accelerator Laboratory). The energy of electrons has been 4 MeV, bunch charge 10-200 pC, repetition rate 1-50 Hz. It was found that the dielectric permittivity and loss tangent, in general, are shifted to the more low frequency range and decreased after electron beam irradiation.
Keywords: Physics; Electronic structure and electrical properties of surfaces